Kehendak Untuk Berkuasa Dan Manusia Unggul Dalam Perspektif Friedrich Nietzche - Luh Putu Santi Pradnyayanti; Desak Made Ayu Indri Safira (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
For humans, knowing who he is and where he came from, what is the purpose of his life, how he lives life consistently, is a different matter. The question of